Managing a company as an integrated enterprise - Vadivelu Selvakumaran (2009)
The main objective of this dissertation is to provide new integrated enterprise paradigm shift to become globally competitive for traditional manufacturing SME's in Singapore by an instance of real case study analysis. Furthermore the new integrated enterprise paradigm can facilitate the SME towards twenty first century by exploring an opportunity through some re-organising integration tools for achieving competitive advantage in the present situation.